Proceedings of the International Conference on Web Search and Web Data Mining - WSDM '08 2008
DOI: 10.1145/1341531.1341558
|View full text |Cite
|
Sign up to set email alerts
|

Can social bookmarking improve web search?

Abstract: Social bookmarking is a recent phenomenon which has the potential to give us a great deal of data about pages on the web. One major question is whether that data can be used to augment systems like web search. To answer this question, over the past year we have gathered what we believe to be the largest dataset from a social bookmarking site yet analyzed by academic researchers. Our dataset represents about forty million bookmarks from the social bookmarking site del.icio.us. We contribute a characterization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
230
1
2

Year Published

2009
2009
2011
2011

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(241 citation statements)
references
References 14 publications
8
230
1
2
Order By: Relevance
“…[14] investigate the overlap between anchortext and tags for a Web page. [9] present an in-depth analysis of the del.icio.us tagging portal and conclude that the data contained in tagging portals represents valuable information which could enhance the performance of search engines. A similar conclusion is drawn by Yanbe et al [24] who also investigate the possibility of a hybrid search approach, based both on PageRank and on social annotations.…”
Section: Related Workmentioning
confidence: 99%
“…[14] investigate the overlap between anchortext and tags for a Web page. [9] present an in-depth analysis of the del.icio.us tagging portal and conclude that the data contained in tagging portals represents valuable information which could enhance the performance of search engines. A similar conclusion is drawn by Yanbe et al [24] who also investigate the possibility of a hybrid search approach, based both on PageRank and on social annotations.…”
Section: Related Workmentioning
confidence: 99%
“…It provides authentication and access control features. Heymann, et al [8], concluded that social bookmarking can provide search data not currently provided by other sources, though it may currently lack the size and distribution of tags necessary to make a significant impact. Santos-Neto, et al [7], showed that the current level of collaboration in CiteULike and Connotea is consistently low.…”
Section: Related Studiesmentioning
confidence: 99%
“…Vander Wal [2] observed that tagging could be used to compensate for missing terms in a taxonomy and Lin et al [3] and Al-Khalifa et al [4] explored the overlap of tags with controlled vocabularies and automatic indexing. Sen et al have studied the quality of tags and tagclouds in [5], Farooq et al [6] focus on folksonomies adding intellectual value to a tagging system, whereas Heymann et al [7] observe that tags are present in the page text of 50% of annotated pages and in 16% of the titles.…”
Section: Introductionmentioning
confidence: 99%